Two newly introduced tropical bark and ambrosia beetles (Coleoptera: Curculionidae, Scolytinae) damaging figs (Ficus carica) in southern Italy - Faccoli, Massimo; Campo, Giuseppe; Perrotta, Giancarlo; Rassati, Davide (Zootaxa, 2016)
In summer 2014, the bark beetle Hypocryphalus scabricollis (Eichhoff) and the ambrosia beetle Xyleborus bispinatus Eichhoff, species new to Italy and Europe, respectively, were found for the first time in south-eastern Sicily (Italy). Large infestations of the two species were recorded in many plantations of common fig (Ficus carica L.) both in 2014 and 2015. Data concerning insect characteristics, taxonomy, and distribution are briefly reported.